(untitled) (Scientific journal of the Fergana State University, 2024)
Nodays it has established that two species belonging to the genus Iskandaria live in the reservoirs of the Fergana Valley, and they are local species. This article talks about the distribution of the Alexandrian species in the reservoirs of the valley.